Escrita das alunas nos jornais estudantis do Atheneu Sergipense (1942-1959) - Santana, Valéria Costa Moraes de (2024)
This dissertation focuses on the writing of female students in the student newspapers of Atheneu Sergipense (1942-1959), an educational institution located in Aracaju/Sergipe. The general objective of the research is to analyze the writings of the female students of Atheneu Sergipense in the student newspapers A Voz do Estudante, O Atheneu, and O Eco, which belonged to Atheneu Sergipense during the specified historical period. The time frame was defined based on the publication dates of the student writings in secondary school newspapers, starting in 1942 (A Voz do Estudante) and ending in 1959 (O Eco), which aligns with the end date of the Project “Os jornais estudantis em Sergipe (1874-1959): práticas educativas pela ótica dos discentes do secundário” (UFS/Universal CNPq/2021), of which this research is a part. For this study, we adopted a methodological approach consistent with historical research and the theoretical assumptions of the History of Education, grounded in Cultural History. The sources used were the student newspapers A Voz do Estudante, O Atheneu, and O Eco themselves, as well as educational legislation, regulations, certificates, and individual student dossiers, including photographs, requests, health certificates, and vaccination records. The sources were primarily located at the Centro de Educação e Memória do Atheneu Sergipense (CEMAS), the Biblioteca Pública Epiphanio Dória (BPED), and the Instituto Histórico e Geográfico de Sergipe (IHGSE). Thus, this work falls within the field of the History of Education, from the perspective of Cultural History, using key concepts: Chartier's representation (1990, 2002), Benito’s school culture (2017), and dialogues with Souza (2008) on secondary education. The study explores how the pages of these newspapers reveal aspects of young women's thoughts on various school and social issues pertinent to Sergipe society in the mid-20th century, as well as their interaction with secondary educational practices. The research also presents the materiality of these newspapers as seen through these writings.